Using interactive teaching methods in higher education - احمد استبرق كاظم عباس (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The research focused on the primary methods of modern education that emphasize independent student activity, the organization of self-learning environments, experimental and practical training. Students have the choice of procedures and can take initiative. Additionally, it emphasizes flexible training programs in which students can work at a comfortable pace. This research aims to study interactive teaching methods in higher education and focuses on the relationship between students and professors in Iraq. It also addresses the use of interactive training methods that encourage interest in the profession, enhance the efficiency of accessing training materials, form behavioral patterns, provide high motivation, strength, knowledge, team spirit, freedom of expression, and, most importantly, contribute to the complex competencies of future specialists. Interactive education is the path to creativity as it develops concepts of life skills in advanced curricula, enabling students to understand the movement of society post-graduation.